Who will Protect the Night’s Watch? Legislative Reform and a State Apparatus for the Comprehensive Shielding of South African Whistleblowers - Radulovic, Ugljesa (NBP. Nauka, bezbednosti, policija, 2025)
South Africa’s recent history has been marred by revelations of state capture, which came to the public fore, in part, because of the disclosures of whistleblowers. These whistleblowers enacted the role of the Night’s Watch, much like the eponymous military order in George R.R. Martin’s A Song of Ice and Fire high fantasy novels. Utilizing a qualitative approach encompassing two research methods, this paper establishes that whistleblowers protected South Africa alone like a fire burning against the cold, being subjected to various forms of retaliation. The frequency and severity of retaliation was the result of inadequate whistleblower protection legislation. In the absence of adequate legislation, it was civil society that interceded to provide the whistleblowers several forms of support. In light of these findings, this paper puts forward recommendations for the comprehensive shielding of South African whistleblowers. It proposes that it is necessary to revise whistleblower protection law by applying provisions from a number of effective global instruments. It also argues for the establishment of an independent state apparatus concerned with supporting whistleblowers and consolidating civil society efforts.